Pleomorphic xanthoastrocytoma with NTRK fusion presenting as spontaneous intracranial hemorrhage-case report and literature review - Yilong Wu; Sze Jet Aw; Swati Jain; Li Yin Ooi; Enrica E. K. Tan; Kenneth T. E. Chang; Harvey J. Teo; Wan Tew Seow; Wan Tew Seow; Wan Tew Seow; Sharon Y. Y. Low; Sharon Y. Y. Low; et al. (Frontiers Media S.A., 2024)
BackgroundPleomorphic xanthoastrocytoma (PXA) is a rare brain tumor that accounts for <1% of all gliomas. An in-depth understanding of PXA's molecular makeup remains a work in progress due to its limited numbers globally. Separately, spontaneous intracranial hemorrhage (pICH) is an uncommon but potentially devastating emergency in young children, often caused by vascular malformations or underlying hematological conditions. We describe an interesting case of a toddler who presented with pICH, later found to have a PXA as the underlying cause of hemorrhage. Further molecular interrogation of the tumor revealed a neurotrophic tyrosine receptor kinase (NTRK) gene fusion and CDKN2A deletion more commonly seen in infantile high-grade gliomas. The unusual clinicopathological features of this case are discussed in corroboration with published literature.Case presentationA previously well 2-year-old male presented with acute drowsiness and symptoms of increased intracranial pressure secondary to a large right frontoparietal intracerebral hematoma. He underwent an emergency craniotomy and partial evacuation of the hematoma for lifesaving measures. Follow-up neuroimaging reported a likely right intra-axial tumor with hemorrhagic components. Histology confirmed the tumor to be a PXA (WHO 2). Additional molecular investigations showed it was negative for BRAFV600E mutation but was positive for CDKN2A homozygous deletion and a unique neurotrophic tyrosine receptor kinase (NTRK) gene fusion. The patient subsequently underwent second-stage surgery to proceed with maximal safe resection of the remnant tumor, followed by the commencement of adjuvant chemotherapy.ConclusionTo date, there are very few pediatric cases of PXA that present with spontaneous pICH and whose tumors have undergone thorough molecular testing. Our patient's journey highlights the role of a dedicated multidisciplinary neuro-oncology team to guide optimal treatment.